AGARICALES OF EASTERN INDIA-I - M. P. SINHA, M. K. DAS* AND (Indian Phytopathology, 2002)
This paper includes detailed and illustrated account of three species of genus Amanita, namely, A. hemibapha (Berk. & Br.) Sacc. var. jalJanica Corner & Bas, A. oualispora Boid. and A. [uiua (Schaeff. ex Fr.) Pers. All the three species are new records for India.